2021
DOI: 10.1002/ccd.29559
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of transcatheter aortic valve replacement in end stage liver and renal disease

Abstract: Objectives This study evaluates in‐hospital, 30‐day, and 1‐year outcomes post‐transcatheter aortic valve replacement (TAVR) in end stage liver disease (ESLD) and/or end stage renal disease (ESRD) compared with patients without these comorbidities. Background TAVR is an alternative to surgical aortic valve replacement in patients with ESLD and ESRD, though current outcomes data are limited. Methods We compared 309 patients (N = 29 ESLD and/or ESRD, N = 280 control) age > 18 who underwent transfemoral TAVR from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…2017 48 C 3 L 1124 85 (82–88) 69.8 6.7 (4.7–9.4) 78.8 Caughron et al. 2021 49 C 6 B 309 78.2 ± 10.3 44.3 5 ± 4.4 75.7 24.3 0 Ando et al. 2020 50 C 4 E 5731 74 ± 10.1 38.1 Feldman et al.…”
Section: Resultsmentioning
confidence: 99%
“…2017 48 C 3 L 1124 85 (82–88) 69.8 6.7 (4.7–9.4) 78.8 Caughron et al. 2021 49 C 6 B 309 78.2 ± 10.3 44.3 5 ± 4.4 75.7 24.3 0 Ando et al. 2020 50 C 4 E 5731 74 ± 10.1 38.1 Feldman et al.…”
Section: Resultsmentioning
confidence: 99%
“…Caughron et al concluded that the mortality at discharge and at 30 days was similar in both groups, suggesting no increased risk initially but with an upward trend of mortality at 1 year after TAVR. 16 Ultimately, this case suggests the potential TAVR has at overcoming the cardiac barriers that are imposed on a successful OLT.…”
Section: Discussionmentioning
confidence: 96%
“…With the development and refinement of percutaneous valve techniques, some of these risks may be mitigated. A retrospective analysis [15] of adults who underwent transfemoral transaortic valve replacement (TAVR) for severe aortic valve disease compared a group of combined ESLD patients ( n = 15) and end-stage kidney disease (ESRD) patients ( n = 17) with non-ESLD/non-ESRD controls ( n = 280). In the ESLD subgroup, there was one vascular event (6.7%) and one patient requiring pacemaker (6.7%), but no cerebrovascular events or mortality during the index hospitalization.…”
Section: Management Of Valvular Disease In Liver Transplant Candidatesmentioning
confidence: 99%